Effects of Different Viewing Conditions on Radiographic Interpretation - Mahkameh Moshfeghi; Majid Shahbazian; Soodabeh Sadat Sajadi; Sepideh Sajadi; Hossein Ansari (Tehran University of Medical Sciences, 2016)
Objectives: Optimum viewing conditions facilitate identification of radiographic details and decrease the need for retakes, patients' costs and radiation dose. This study sought to evaluate the effects of different viewing conditions on radiographic interpretation. Materials and Methods: This diagnostic study was performed by evaluating radiograph of a 7mm-thick aluminum block, in which 10 holes with 2mm diameters were randomly drilled with depths ranging from 0.05 mm to 0.50mm. The radiograph was viewed by four oral radiologists independently under four viewing conditions, including a white light viewing light box in a lit room, yellow light viewing light box in a lit room, white light viewing light box in a dark room and yellow light viewing light box in a dark room. Number of circular shadows observed on the film was recorded. The data were analyzed by two-way ANOVA. Results: The mean number of detected circular shadows was 6.75, 7.5, 7.25 and 7.75 in white light viewing light box in a lit room, white light viewing light box in a dark room, yellow light viewing light box in a lit room and yellow light viewing light box in a dark room, respectively. Although the surrounding illumination had statistically significant effect on the radiographic details (P≤0.03), the light color of the viewing light box had no significant effect on visibility of the radiographic details. Conclusion: White and yellow light of the viewing light box had no significant effect on visibility of the radiographic details but more information was obtained in a dark room.